2014
DOI: 10.4142/jvs.2014.15.4.529
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and characterization of livestock-associated methicillin-resistantStaphylococcus aureusin pig industries of northern Thailand

Abstract: This study was conducted to determine the prevalence of livestock-associated methicillin-resistant Staphylococcus aureus (LA-MRSA) in pigs, farm workers, and the environment in northern Thailand, and to assess LA-MRSA isolate phenotypic characteristics. One hundred and four pig farms were randomly selected from the 21,152 in Chiang Mai and Lamphun provinces in 2012. Nasal and skin swab samples were collected from pigs and farm workers. Environmental swabs (pig stable floor, faucet, and feeder) were also collec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
29
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 30 publications
3
29
1
Order By: Relevance
“…Coagulase-positive Staphylococcus (CPS), particularly S. aureus, can colonize both humans and animals (Sung et al, 2008). The present study showed that the rate of MRSA colonization among pig farmers (3.1 %) and pigs (0.6 %) was similar to the rates found in a recent study from northern Thailand, which reported that the prevalence of nasal MRSA carriers in pig-farm workers and pigs was 1.28 % (4/312) and 0.68 % (2/292), respectively (Patchanee et al, 2014). These rates are lower than those reported in Europe and North America, but are somewhat comparable to those of Asian countries such as China (Fang et al, 2014).…”
Section: Bacterial Isolatessupporting
confidence: 89%
See 1 more Smart Citation
“…Coagulase-positive Staphylococcus (CPS), particularly S. aureus, can colonize both humans and animals (Sung et al, 2008). The present study showed that the rate of MRSA colonization among pig farmers (3.1 %) and pigs (0.6 %) was similar to the rates found in a recent study from northern Thailand, which reported that the prevalence of nasal MRSA carriers in pig-farm workers and pigs was 1.28 % (4/312) and 0.68 % (2/292), respectively (Patchanee et al, 2014). These rates are lower than those reported in Europe and North America, but are somewhat comparable to those of Asian countries such as China (Fang et al, 2014).…”
Section: Bacterial Isolatessupporting
confidence: 89%
“…The first report of ST9 MRSA from pigs and farm workers in Asia was from China (Cui et al, 2009). Since then, many reports of ST9 LA-MRSA were made (Guardabassi et al, 2009;Neela et al, 2009;Vestergaard et al, 2012;Patchanee et al, 2014;Fang et al, 2014). Our study confirmed that ST9 MRSA was an endemic LA-MRSA strain in pigs and pigfarm workers in the Khon Kaen province of Thailand.…”
Section: Genotypes Of Mrssupporting
confidence: 82%
“…aureus clonal complex (CC) 398 is a particular S. aureus strain commonly found in livestock and its emergence and dissemination has received global attention (Smith and Pearson, 2011). However, researchers have since documented that CC398 is not the only S. aureus strain circulating in the IHO environment; CC9 is being observed in hogs and IHO workers in the United States (Nadimpalli et al, 2014) and in hogs and IHO workers in Asia (Patchanee et al, 2014;Ye et al, 2016). Furthermore, among these and other lineages, there is evidence that genetic markers may distinguish livestock-from human-adapted clades among the CC398 and CC9 genotypes commonly associated with livestock (Sung et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, another MRSA clone emerged in the community, which was observed in livestock and related workers and was referred to as livestock-associated MRSA (LA-MRSA) (3). Livestock, especially pigs, can serve as reservoirs for LA-MRSA, and the bacteria can also be transmitted to humans in close contact with MRSAcolonized animals (4,5).…”
mentioning
confidence: 99%